New Arylalkylamine N-Acetyltransferase in Silkworm (Bombyx mori) Affects Integument Pigmentation - Long, Yaohang; Li, Jiaorong; Zhao, Tianfu; Li, Guannan; Zhu, Yong (Applied biochemistry and biotechnology, 2015)
Dopamine is a precursor for melanin synthesis. Arylalkylamine N-acetyltransferase (AANAT) is involved in the melatonin formation in insects because it could catalyze the transformation from dopamine to dopamine-N-acetyldopamine. In this study, we identified a new AANAT gene in the silkworm (Bombyx mori) and assessed its role in the silkworm. The cDNA of this gene encodes 233 amino acids that shares 57 % amino acid identity with the Bm-iAANAT protein. We thus refer to this gene as Bm-iAANAT2. To investigate the role of Bm-iAANAT2, we constructed a transgenic interference system using a 3xp3 promoter to suppress the expression of Bm-iAANAT2 in the silkworm. We observed that melanin deposition occurs in the head and integument in transgenic lines. To verify the melanism pattern, dopamine content and the enzyme activity of AANAT were determined by high-performance liquid chromatography (HPLC). We found that an increase in dopamine levels affects melanism patterns on the heads of transgenic B. mori. A reduction in the enzyme activity of AANAT leads to changes in dopamine levels. We analyzed the expression of the Bm-iAANAT2 genes by qPCR and found that the expression of Bm-iAANAT2 gene is significantly lower in transgenic lines. Our results lead us to conclude that Bm-iAANAT2 is a new arylalkylamine N-acetyltransferase gene in the silkworm and is involved in the metabolism of the dopamine to avoid the generation of melanin.